FORMATION OF JUNIOR SCHOOLCHILDREN’S ELEMENTAL MYCOLOGICAL REPRESENTATIONS AND CONCEPTS IN AT THE LESSONS "I EXPLORE THE WORLD" - Borys, Uliana (Mountain School of Ukrainian Carpaty, 2021)
The article is devoted to the formation of elementary mycological ideas and concepts in primary schoolchildren at the lessons "I explore the world". It is emphasized that natural ideas and concepts in schoolchildren are formed during the study of natural education, in the context of the integrated course "I explore the world". There are analyzed the pedagogical conditions for the selection of teaching methods and techniques during the formation of elementary mycological ideas and concepts in primary schoolchildren at the lessons "I explore the world". It is concluded that the system of visual teaching methods is directly related to the system of teaching aids, in particular visual aids, a comprehensive approach to the use of which in combination with the teacher’s word gives the necessary educational effect. The particular importance is given to practical methods, which are a complex interaction of word, clarity and practical work. Practical teaching methods play an important role in the formation of skills and abilities how to apply the acquired knowledge about mushrooms. During the formation of mycological ideas and concepts, the main practical activity of students is to perform a variety of practical tasks, exercises, didactic games. Based on the analysis of account the age characteristics of primary schoolchildren, the content of natural material, generally accepted conditions of knowledge formation, it is established that the effectiveness of the process of knowledge formation of primary schoolchildren depends on material; observance of step-by-step formation of natural ideas and concepts; selection and combination of different methods and means of teaching during the formation of knowledge. psychological, pedagogical and methodological literature, taking into